Poverty reduction through the development of inclusive food value chains - Vos, Rob; Cattaneo, Andrea (Chinese Academy of Agricultural Sciences, 2021)
Propelled by urbanization, rising incomes, and changing diets, food markets have been expanding in Africa and South Asia, creating the vast potential for job and income opportunities along food supply chains and, hence, for poverty reduction. The novel coronavirus (COVID-19) that spread to a pandemic in early 2020 provokes enormous setbacks to this expansion. This, however, should provide lessons regarding the importance of resilient and inclusive food systems. Emergency responses to COVID-19 should consider interventions towards that end and leverage the opportunities provided by food markets growth as economies recover from the present economic recession. This paper assesses options of how this could be done by facilitating the better functioning and interconnectedness of the many small and medium-sized enterprises that are proliferating along the “hidden middle” of food value chains in storage, logistics, transportation, and wholesale and retail distribution. It also explores how policies can help smallholder farmers connect to this “hidden middle” in more gainful ways and help them climb out of poverty as well.